Detection of specific antibody isotypes and subtypes before and after treatment of American visceral leishmaniasis - da Matta, Vânia L.R. (J Clin Lab Anal, 2000)
Sera from patients with American visceral leishmaniasis (AVL) were studied before and after treatment based on their antibody isotypes and subtypes. The study was comprised of 33 Brazilian patients with well‐defined diagnosis of AVL and 39 clinically healthy individuals. Antileishmanial antibody isotypes and subtypes were observed in almost all patients, except IgA that was detected in about 63% of them. The sensitivity and specificity of the immunofluorescence assay in the detection of antibody isotypes (IgG and IgM) and subtypes (IgG1, IgG2, IgG3, and IgG4) were high with no statistical difference, ranging from 0.937 to 1.000 and from 0.954 to 1.000, respectively. All IgG antibodies and its subtypes had their levels reduced after treatment. However, the IgG4 had an early decay and its conversion to negative was significantly high in children. Moreover, the profile of IgG4 before treatment corresponded to a unimodal curve that shifted to a patent bimodal curve after treatment, indicative of therapeutic success. Thus, the IgG4 shows to be a suitable immunological marker for the assessment of chemotherapy in AVL patients or communities. Our findings suggest that IgG4 correlates with IL‐4 that also decreases after therapy. J. Clin. Lab. Anal. 14:5–12, 2000. © 2000 Wiley‐Liss, Inc.